Teenage Labor Migration and Antitrafficking Policy in West Africa. Issue 1 (May 2014) - Howard, Neil
Within the antitrafficking community, even legal child or youth work is often pathologized, seen as a "worst form of child labor" or, where movement is involved, as trafficking. Major policy responses thus focus on attempting to protect the young by preventing their movement or policing their work. Using a case study of adolescent labor migrants in Benin who work in artisanal gravel quarries in Nigeria, I provide evidence that suggests that the dominant discourse regarding this kind of labor is inaccurate and that policies based on it may be failing. This is in large part because the labor migration depicted as "trafficking" by the antitrafficking community is not experienced as such by young migrants.